The Impact of Adaptive Leadership on Medical Team Performance in Emergency Units - Yuliaty, Farida; Amalia, Nafrah (Amkop Management Accounting Review (AMAR), 2025)
This study investigates the influence of adaptive leadership style on the effectiveness of medical teams in emergency situations within the Emergency Unit. Employing a qualitative case study approach, the findings reveal that adaptive leadership positively contributes to team performance during critical incidents. Key characteristics of adaptive leaders—such as strategic thinking, empathetic engagement, and self-corrective learning—enhance nurse performance and overall team responsiveness. The study offers valuable insights for leadership development strategies in emergency healthcare settings.